ISOLATION AND MOLECULAR CHARACTERIZATION OF Campylobacter jejuni FROM LOCAL BROILER CHICKEN (LBC) AND FROZEN IMPORTED CHICKENS (IFC) IN DUHOK PROVINCE, KURDISTAN REGION- IRAQ - Ghaffar, Nacheervan M.; Mohialdeen, Niwar H. (Science Journal of University of Zakho, 2023)
Campylobacter jejuni is one of the major foods borne pathogen that cause diarrhea in human. Consumption of undercooked poultry meats and its by-products is believed to be the main source of human campylobacteriosis.  This study aims to determine the prevalence of this bacteria in LBC and IFC using conventional culture methods and conventional PCR assay, with molecular identification by sequencing of 16S rRNA. Two hundred and twenty-five samples from LBC (n=150) and IFC (n=75) were collected. Conventionally, overall, 21.3% (n = 48) were identified as C. jejuni. In LBC 30% (45/150), from this 9% and 72% identifies as C. jejuni when used enrichment and direct isolation method, respectively. Generally, the PCR confirmed 53.3% from LBC and 66.6% from IFC to be C. jejuni.  All isolates were strongly resistant to Tetracycline, Ciprofloxacin, Nalidixic acid, and Oxytetracycline, while susceptible to Erythromycin and Gentamycin. Therefore,  they were considered as Multi drug resistant strains. Based on the 16S rRNA sequencing, LBC and IFC  were similar and genetically related to each other. Comparing with respective databases in NCBI, these isolates  had the variation in their closeness with different strains from other countries isolated from different sources. Further study  recommended, related to the virulence genes, physio-morphological characteristic, and whole genome sequencing of some isolated strains.
Keywords: C. jejuni, hipo; (110) GaAs; antibiotics resistant; phylogenetic tree